1991
DOI: 10.1016/0167-4889(91)90200-h
|View full text |Cite
|
Sign up to set email alerts
|

Priming effect of glucagon-like peptide-1 (7–36) amide, glucose-dependent insulinotropic polypeptide and cholecystokinin-8 at the isolated perfused rat pancreas

Abstract: The priming effect of glucagon-like peptide-1 (7-36) amide (GLP-1 (7-36) amide), glucose-dependent insulin-releasing polypeptide (GIP) and cholecystokinin-8 (CCK-8) on glucose-induced insulin secretion from rat pancreas was investigated. The isolated pancreas was perfused in vitro with Krebs-Ringer bicarbonate buffer containing 2.8 mmol/l glucose. After 10 min this medium was supplemented with GLP-1 (7-36) amide, GIP or CCK-8 (10, 100, 1000 pmol/l) for 10 min. After an additional 10 min period with 2.8 mmol/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…This is in agreement with other studies where no, or only a small, increase in plasma insulin concentrations was seen at low plasma glucose concentrations and plasma GLP-1 concentrations around 16 pmol·l -1 [49,53]. In vitro studies have shown that GLP-1 has a priming effect on glucosestimulated insulin secretion [50,54] but in vivo pretreatment with GLP-1 for 60 min did not alter the subsequent beta-cell response to glucose [49]. Therefore, the increase in plasma GLP-1 concentrations during the glucose infusion is probably more physiologically relevant to affect insulin secretion than the high plasma GLP-1 concentrations before the clamp.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with other studies where no, or only a small, increase in plasma insulin concentrations was seen at low plasma glucose concentrations and plasma GLP-1 concentrations around 16 pmol·l -1 [49,53]. In vitro studies have shown that GLP-1 has a priming effect on glucosestimulated insulin secretion [50,54] but in vivo pretreatment with GLP-1 for 60 min did not alter the subsequent beta-cell response to glucose [49]. Therefore, the increase in plasma GLP-1 concentrations during the glucose infusion is probably more physiologically relevant to affect insulin secretion than the high plasma GLP-1 concentrations before the clamp.…”
Section: Discussionsupporting
confidence: 92%
“…The anti-insulin monoclonal antibody was from Sigma. The anti-IGF-1 receptor and anti-insulin receptor antibodies were from Santa Cruz Biotechnology; both antibodies were raised against the N-terminal unique sequences (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the corresponding receptor. IGF-1 was from Becton Dickinson or GIBCO͞BRL.…”
Section: Methodsmentioning
confidence: 99%
“…Many insulin secretagogues that utilize cAMP as a second messenger will potentiate glucose-stimulated insulin secretion (1,8,9), and agents that elevate cAMP, such as nonspecific phosphodiesterase (PDE) inhibitors (e.g., isobutylmethylxanthine and theophylline), are potent insulin secretagogues (10)(11)(12). Several recent studies have suggested the presence of both PDE3 and PDE4 activities within pancreatic islets (for a review about various types of PDEs, see ref.…”
mentioning
confidence: 99%
“…A short lasting preinfusion of GLP-l(7-36) amide, GIP, and CCK induced an augmented insulin secretion in response to subsequent glucose stimulation [58].…”
Section: ( 4 ) Interaction Of Glp-1(7-36) Amide With Other Hormonesmentioning
confidence: 99%